Peripheral Hybrid CB1R and iNOS Antagonist MRI-1867 Displays Anti-Fibrotic Efficacy in Bleomycin-Induced Skin Fibrosis - Zawatsky, Charles N.; Park, Joshua K.; Abdalla, Jasmina; Kunos, George; Iyer, Malliga R.; Cinar, Resat (Frontiers in Endocrinology, 2021)
Scleroderma, or systemic sclerosis, is a multi-organ connective tissue disease resulting in fibrosis of the skin, heart, and lungs with no effective treatment. Endocannabinoids acting via cannabinoid-1 receptors (CB1R) and increased activity of inducible NO synthase (iNOS) promote tissue fibrosis including skin fibrosis, and joint targeting of these pathways may improve therapeutic efficacy. Recently, we showed that in mouse models of liver, lung and kidney fibrosis, treatment with a peripherally restricted hybrid CB1R/iNOS inhibitor (MRI-1867) yields greater anti-fibrotic efficacy than inhibiting either target alone. Here, we evaluated the therapeutic efficacy of MRI-1867 in bleomycin-induced skin fibrosis. Skin fibrosis was induced in C57BL/6J (B6) and Mdr1a/b-Bcrp triple knock-out (KO) mice by daily subcutaneous injections of bleomycin (2 IU/100 µL) for 28 days. Starting on day 15, mice were treated for 2 weeks with daily oral gavage of vehicle or MRI-1867. Skin levels of MRI-1867 and endocannabinoids were measured by mass spectrometry to assess target exposure and engagement by MRI-1867. Fibrosis was characterized histologically by dermal thickening and biochemically by hydroxyproline content. We also evaluated the potential increase of drug-efflux associated ABC transporters by bleomycin in skin fibrosis, which could affect target exposure to test compounds, as reported in bleomycin-induced lung fibrosis. Bleomycin-induced skin fibrosis was comparable in B6 and Mdr1a/b-Bcrp KO mice. However, the skin level of MRI-1867, an MDR1 substrate, was dramatically lower in B6 mice (0.023 µM) than in Mdr1a/b-Bcrp KO mice (8.8 µM) due to a bleomycin-induced increase in efflux activity of MDR1 in fibrotic skin. Furthermore, the endocannabinoids anandamide and 2-arachidonylglycerol were elevated 2-4-fold in the fibrotic vs. control skin in both mouse strains. MRI-1867 treatment attenuated bleomycin-induced established skin fibrosis and the associated increase in endocannabinoids in Mdr1a/b-Bcrp KO mice but not in B6 mice. We conclude that combined inhibition of CB1R and iNOS is an effective anti-fibrotic strategy for scleroderma. As bleomycin induces an artifact in testing antifibrotic drug candidates that are substrates of drug-efflux transporters, using Mdr1a/b-Bcrp KO mice for preclinical testing of such compounds avoids this pitfall.